Misread Signals: Perception, Emotion, and Nonverbal Conflicts on Bandung Streets - Ira Lusiawati (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
Roadways are not merely functional spaces for vehicular movement but also complex arenas of social communication. In the city of Bandung, road users' diverse social and cultural backgrounds increase the potential for misinterpretations of nonverbal communication, often escalating into verbal and even physical conflicts. This study aims to analyze the factors influencing shifts in road users' perceptions, the mechanisms behind nonverbal communication failures, and the role of emotional control in mitigating traffic conflicts. This research uses a qualitative approach, participatory observation, and document analysis methods. Observations were conducted at several strategic locations in Bandung, such as the Dago, Setiabudi, and Buah Batu areas, to capture the nonverbal behaviors of road users authentically. The findings reveal that situational pressures, biases from past experiences, and emotional states of road users trigger perception shifts. Communication failures occur through misinterpretations of nonverbal symbols, weak emotional control, and conflict escalation. Emotional control is key to restraining aggressive responses and minimizing misunderstandings. This study concludes by emphasizing the importance of integrating emotional education into traffic safety campaigns. By strengthening emotional awareness and symbol comprehension, it is hoped that a safer, more harmonious, and humanistic traffic culture will be cultivated in Bandung.